2016
DOI: 10.1097/scs.0000000000003042
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle Tongue Flap for Palatal Fistula Closure

Abstract: The use of anterior pedicle tongue flap for closing palatal fistulae demonstrates to be a safe procedure with high success rates (81% in this paper) when correctly indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…9,10,13–25 Despite the fact that tongue flap has been proven to be a sturdy, reliable, and efficient means for the closure of hard palate fistula especially in the anterior region, there existed unsuccessful cases due to the over mobility of tongue, and sometimes the massive size of fistula. 4,10,26 For the unique case presented in this article, the anterior fistula due to its irregular shape and extended size of 4.5 × 5 cm was by far the largest fistula comparing with the ones reported in literature. In our case, a double anterior pedicle tongue flaps was designed for the patient based on the following reasons and principles: Firstly, tongue was divided into right and left halves by a medial fibrous septum.…”
Section: Discussionmentioning
confidence: 58%
“…9,10,13–25 Despite the fact that tongue flap has been proven to be a sturdy, reliable, and efficient means for the closure of hard palate fistula especially in the anterior region, there existed unsuccessful cases due to the over mobility of tongue, and sometimes the massive size of fistula. 4,10,26 For the unique case presented in this article, the anterior fistula due to its irregular shape and extended size of 4.5 × 5 cm was by far the largest fistula comparing with the ones reported in literature. In our case, a double anterior pedicle tongue flaps was designed for the patient based on the following reasons and principles: Firstly, tongue was divided into right and left halves by a medial fibrous septum.…”
Section: Discussionmentioning
confidence: 58%
“…Surgeons in the present study recommended that tongue flaps only be used if the patient will cooperate and would rarely use them before the age of 5 years. Recent retrospective studies of fistula repair with tongue flaps have suggested fistula recurrence rates of 8% to 10% (Mahajan et al, 2014; Sodhi et al, 2014; Strujak et al, 2016), although Saralaya et al (2019) reported a recurrence rate of 30% (4/13) for more complex fistulae. Despite the robustness of tongue flaps, a recent study comparing FAMM flaps and tongue flaps for anterior palatal fistula closure found that the 2 approaches had similar effectiveness (0% recurrence), but the FAMM flap required less operative time and had fewer postoperative speech and feeding issues (Sohail et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Palatal fistula has a high rate of recurrence following repair. It was reported by Strujak et al, that fistula rates range as high as 58% after primary repair, and up to an average recurrence rate of nearly 33% after fistula repair [10] we thought of improving the wound healing process, and having noted the benefits of PRP offered in other surgical procedures, we decided to study if its application with palatal fistula repair could decrease the recurrence rate.…”
Section: Discussionmentioning
confidence: 99%